A middleware for information processing in mobile computing platforms. (8th July 2008) - Shriram, R.; Sugumaran, Vijayan; Vivekanandan, K.
The emergence of small, resource-constrained, and highly mobile computing platforms presents numerous challenges in developing and providing new services for users on the move. These challenges demand architectures and infrastructures that are scalable, reliable, secure and personalised. Recently, middleware has emerged as one of the key solutions for supporting next generation ubiquitous communication, and providing additional personalised services over and above those provided by existing networks. To this end, this paper presents the design of a community network-based middleware system for providing personalised information access to mobile users. The paper also discusses a prototype that has been implemented to validate and demonstrate the features of the middleware. Initial results regarding usability, flexibility, transcoding, memory efficiency and display rendering efficiency are discussed. Future work for the mobile middleware and research directions are outlined.